2018
DOI: 10.1002/adfm.201804343
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Multifunctional Self‐Propelled Paramagnetic Microrobots with Chemical Handles for Cell Manipulation and Drug Delivery

Abstract: Autonomous self-propelled micromachines, taking energy from surrounding environment and converting it to their motion, are on the forefront of the research for smart materials in the recent years. Owing to their self-propulsion mechanism, they have demonstrated to be more efficient drug carriers than passive particles. Here, multifunctional superparamagnetic/catalytic microrobots (PM/Pt microrobots) for cell manipulation, anticancer drug loading, and delivery to breast cancer cells are presented. These PM/Pt m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 54 publications
0
91
0
Order By: Relevance
“…Micro/nanomotors have been regarded as one exciting research field owing to their huge potential in biomedical application 13 . Up to now, they are divided into three categories according to their propulsion modes: physical, biological, and chemical.…”
Section: Introductionmentioning
confidence: 99%
“…Micro/nanomotors have been regarded as one exciting research field owing to their huge potential in biomedical application 13 . Up to now, they are divided into three categories according to their propulsion modes: physical, biological, and chemical.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the micro/nanorobot was functionalized with tosyl groups on its outer surface, which served to bind cancer cells through their surface and load drugs such as doxorubicin. [152] Pharmaceutical agents have also been entrapped directly on the surface of micro/nanorobots by using electrostatic interactions. The use of electrostatic forces was reported to load the positively charged brilliant green antiseptic drug into a negatively charged polypyrrole-polystyrene sulfonate segment of an ultrasound propelled nanorobot.…”
Section: Pharmaceutical Drugsmentioning
confidence: 99%
“…Therefore, a series of synthetic micro/ nanomotors have been designed to harness local H 2 O 2 as an energy source for propulsion to demonstrate the delivery performance. For example, Villa et al [61] reported multifunctional superparamagnetic/catalytic microrobots (PM/ Pt microrobots) for cell manipulation and anticancer drug delivery ( Fig. 2a).…”
Section: Extracellular Delivery Systemmentioning
confidence: 99%